2011
DOI: 10.1177/1534735411413265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sweet Bee Venom Pharmacopuncture Treatment for Chemotherapy-Induced Peripheral Neuropathy

Abstract: This safety results of the SBVP therapy merits further investigations in a larger size trial for it to develop into a potential intervention for managing CIPN symptoms. This study will be extended to a dose-response evaluation to further establish safety and response, prior to a randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…Moreover, as research continues into the role of pharmacological agents for treatment and/or prevention of oxaliplatin-induced peripheral neuropathy; interest in nonpharmacological treatment options is increasing. Studies have been lacking on non-pharmacological therapy for the treatment of oxaliplatin-peripheral neuropathy, although some clinical studies have been performed on acupuncture for the treatment of chemotherapy-induced peripheral neuropathy [39][40][41][42]. These studies reported improvements following acupuncture in the Visual Analog System (VAS) pain scale, gait, and nerve conduction tests, and reduced use of pain medication.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, as research continues into the role of pharmacological agents for treatment and/or prevention of oxaliplatin-induced peripheral neuropathy; interest in nonpharmacological treatment options is increasing. Studies have been lacking on non-pharmacological therapy for the treatment of oxaliplatin-peripheral neuropathy, although some clinical studies have been performed on acupuncture for the treatment of chemotherapy-induced peripheral neuropathy [39][40][41][42]. These studies reported improvements following acupuncture in the Visual Analog System (VAS) pain scale, gait, and nerve conduction tests, and reduced use of pain medication.…”
Section: Discussionmentioning
confidence: 96%
“…Given that most of its usage and relevant studies are from locally limited area, some consideration may be required before it is used worldwide, but the amount of data is increasing continuously [50] and so far the results are promising [51, 52]. For instance, a case series of bee venom pharmacopuncture for chemotherapy-induced peripheral neuropathy reported improvement of symptoms in patients and, importantly, there were no related AEs [52]. There was also a noticeable pilot study from University of California, San Francisco, that tested pharmacopuncture for primary dysmenorrhea, and they suggested that pharmacopuncture is highly acceptable among American women as well [51].…”
Section: Discussionmentioning
confidence: 99%
“…Adapted from https://www.dolcera.com/wiki/index.php?title=Diabetes products and services. and neuritis [14,15,17,19,[24][25][26][27][28]. Recent studies also confirmed that melittin can significantly reduce blood glucose via insulin secretion and glucose uptake in animal models [21][22][23].…”
Section: Introductionmentioning
confidence: 91%